The Investigation of Students’ Motivation in Learning English at SMAN 3 Payakumbuh - Nazfa, Salsa bila; Ayudhia, Honesty Yonanda (Universitas Negeri Padang, 2024)
This study investigates the level of motivation of eleventh grade students at SMAN 3 Payakumbuh in learning English. It also aims to identify what students need in order to increase their motivation. As motivation plays an important role in language learning, fostering desire and enthusiasm for the subject is crucial. This study used a survey method, a quantitative research type. A questionnaire with a five-point Likert scale was used to measure students' motivation. The study involved 101 eleventh grade students selected through total sampling. The results showed an average intrinsic motivation score of 3.16, which was categorized as moderate. Similarly, the mean extrinsic motivation score was 2.67, also indicating a moderate level. Based on the overall score of 2.91 and the Likert scale interpretation, showed moderate to low levels of motivation overall. To address this, this study explored potential students' needs to increase motivation. The results shows that the most preferred approach (with an average score of 3.23 of students choosing it) involved teachers incorporating various learning media such as songs, movies and English learning apps.